STABLECOINS, CENTRAL BANK DIGITAL CURRENCIES, AND THE FUTURE OF THE MONETARY SYSTEM - Marjona, Kurbanbayeva; Nurhayati, Netti; Hendrayati, Heny; Qudratov, Inomjon (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Stablecoins and central bank digital currencies (CBDCs) have moved to the center of debates on the future of money because both instruments combine technological innovation with questions of payment efficiency, monetary sovereignty, legal design, and financial stability. This article examines how private digital money in the form of stablecoins and public digital money in the form of CBDCs may reshape the monetary system. The study uses a structured qualitative review based only on the user’s original article and analyzes official publications from institutions such as the Bank for International Settlements (BIS), International Monetary Fund (IMF), Financial Stability Board (FSB), European Central Bank (ECB), CPMI-IOSCO, and selected central bank studies. The review finds that stablecoins may improve payment speed, programmability, and some cross-border transactions, but they also create risks related to reserve quality, run behavior, deposit substitution, market concentration, and foreign-currency dependence. CBDCs are being explored not simply as digital cash replacements, but as strategic public instruments that may preserve the role of central bank money, support competition in payments, and strengthen resilience in a more tokenised financial environment. The article argues that the most plausible future is not a single dominant form of digital money, but a hybrid architecture in which cash, reserves, bank deposits, tokenised deposits, regulated stablecoins, fast payment systems, and selected forms of CBDC coexist. The main policy implication is that public money must remain the anchor of trust in digital environments while private innovation develops within a strong framework of interoperability, prudential safeguards, and consumer protection.